Efficacy of psychosocial intervention in patients with mild Alzheimer's disease: the multicentre, rater blinded, randomised Danish Alzheimer Intervention Study (DAISY). (17th July 2012) - Waldorff, F B; Buss, D V; Eckermann, A; Rasmussen, M L H; Keiding, N; Rishøj, S; Siersma, V; Sørensen, J; Sørensen, L V; Vogel, A; Waldemar, G
Abstract : Objective To assess the efficacy at 12 months of an early psychosocial counselling and support programme for outpatients with mild Alzheimer's disease and their primary care givers. Design Multicentre, randomised, controlled, rater blinded trial. Setting Primary care and memory clinics in five Danish districts. Participants 330 outpatients with mild Alzheimer's disease and their 330 primary care givers. Interventions Participating dyads (patient and primary care giver) were randomised to control support during follow-up or to control support plus DAISY intervention (multifaceted and semi-tailored counselling, education, and support). Main outcome measures Primary outcomes at 12 months for patients were change from baseline in mini mental state examination (MMSE) score, Cornell depression scale score, and proxy rated European quality of life visual analogue scale (EQ-VAS) score. For care givers, outcomes were change from baseline in geriatric depression scale (GDS 30 items) score and EQ-VAS score. Results Because of multiple testing, statistical significance was set at an adjusted P limit of <0.0005. At 12 months there were no significant differences between the two allocation groups in changes from baseline in the primary and secondary outcomes. However, although non-significant with the adjusted P limit, a small difference was observed for one of the primary patient outcomes (Cornell depression scale score) in patients in favour of the DAISY intervention group before and after adjusting for attrition (P=0.0146 and P=0.0103 respectively). Conclusions The multifaceted, semi-tailored intervention with counselling, education, and support for patients with mild Alzheimer's disease and their care givers did not have any significant effect beyond that with well structured follow-up support at 12 months after adjustment for multiple comparisons. The small positive effect found in the unadjusted primary outcome addressing depressive symptoms in patients may call for further research focusing on patients with Alzheimer's disease and comorbid depression. Trial registration ISRCTN74848736 .